Implementation of the Grand Design of Smart ASN Development at Kantor Regional XII Badan Kepegawaian Negara Pekanbaru - Siti Khaeromah; Febri Yuliani; Hasim As'ari; Saipul Al sukri (Jurnal Manajemen Pelayanan Publik, 2023)
State Civil Apparatus (Aparatur Sipil Negara, abbreviated as ASN) has a crucial role in the success of the bureaucratic reform agenda in government organizations. As executors of government tasks, ASN must meet the demands of a strategic environment marked by the development of the digital world (digital revolution). This study aims to explain the Grand Design of Smart ASN Development and evaluate the implementation of Smart ASN characteristics in Kantor Wilayah XII Badan Kepegawaian Negara Pekanbaru. The research was conducted using a qualitative descriptive method. Data collection was carried out through in-depth interviews, observation, and documentation. Based on the study results, implementing the Grand Design for Smart ASN Development is influenced by factors such as employee composition, digital infrastructure, knowledge management systems, the Team for the Acceleration of Bureaucratic Reform, and the role of agents of change. The output of the Smart ASN program can be seen in improving performance, increasing the achievement of integrity zones and merit systems, improving the quality of human resources through increasing the ASN professionalism index, and increasing welfare. Finally, the results of this research are expected to contribute to the development of Strategic Human Resource Management (SHRM) in developing Smart ASNs in the digital era.